Well posedness and stability result for a thermoelastic laminated Timoshenko beam with distributed delay term. (7th July 2020) - Choucha, Abdelbaki; Ouchenane, Djamel; Boulaaras, Salah
Abstract : In this work, we consider a linear thermoelastic laminated timoshenko beam with distributed delay, where the heat conduction is given by cattaneoâs law. we establish the well posedness of the system. For stability results, we prove exponential and polynomial stabilities of the system for the cases of equal and nonequal speeds of wave propagation.